Gender Differences on Periodontal Diseases Among Type Ii Diabetic Patients in Dhaka (Journal of Chittagong Medical College Teachers' Association, 2016)
Periodontal disease is a slowly progressing disease but the tissue destruction that occurs is largely irreversible. Diabetes mellitus is a notorious risk factor for periodontal disease. It is a cross-sectional type of observational study. Purposively selected 190 diabetic patients, diagnosed by previously oriented dentists at outdoor of BDCH, BIRDEM & SSMCH during June 2014- November 2014 (Six months). Collected data was recorded in a pre-tested checklist and statistically managed using SPSS Verson 20. To find out the most prevalent gender based of specific age groups of people in case of periodontal disease and type II diabetes mellitus; gap between knowledge and practice we had conducted the study. Total 190 patients were studied. Male & female patients represented equally i.e. 95 & 95. About 74.7% female and 66.3% male were from urban area. Age range 30-65 years. All respondents were literate (Can read, write & understand simple math). Respondents have been gone through both physical and full mouth examination based on RBS and CPITN index, labeled as suffering from diabetes and periodontal diseases. The study findings revealed, 68.3% male and 71.6%female was aware about the complications of type 2 Diabetes Mellitus. 82.1% male and 72.6% female consumes carbohydrate rich foods. Based on the CPITN index 68.4% male and 52.6% female were presented with features of gingivitis, 71.6% male and 44.2% female were presented with features of Periodontitis. Rate of Periodontal disease is higher among diabetic patients & there is male preponderance. Ensuring oral hygiene periodontal disease could be reduced significantly. Further in-depth studies are necessary to extract other relevant information in this regard.JCMCTA 2016 ; 27 (1) : 28 - 32